Examining CLIL’s Influence on EFL Learners’ Oral Proficiency Development - Fachria Yamin Marasabessy; Awaludin Rizal; Abdulhalim Daud; Siti Hadianti (Universitas Sulawesi Barat, 2026)
This study investigates the influence of Content and Language Integrated Learning (CLIL) on the development of oral proficiency among English as a Foreign Language (EFL) learners. Addressing a notable gap in the literature regarding effective strategies for enhancing communicative competence, particularly speaking skills, this research explores how integrating subject content with English instruction impacts learners’ oral abilities. Employing a qualitative methodology within a university students' CLIL program, data were collected through semi-structured interviews, classroom observations, and student reflective journals. Findings reveal that CLIL fosters increased willingness to speak, as learners are motivated by both content engagement and the expectation to articulate their understanding in English. Students report that conceptual mastery is a prerequisite for confident and meaningful oral expression, though challenges such as limited vocabulary and the complexity of material can hinder fluency. Interactive classroom practices—including discussions, debates, group projects, and presentations—are perceived as critical to acquiring communicative competence, providing authentic contexts for language use and peer collaboration. Lecturers and students alike observe notable gains in fluency, confidence, and the use of academic vocabulary over time, though emotional barriers such as fear of mistakes and anxiety about performance persist. The study emphasizes the necessity of supportive, student-centered environments and targeted scaffolding to address both linguistic and affective challenges. By illuminating the mechanisms and outcomes of CLIL in EFL contexts, the research provides valuable insights to educators and policymakers striving to enhance oral proficiency through integrated content and language instruction.